PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA MINANG FANTASI KOTA PADANG PANJANG - Zelmiati, Zelmiati; Waryono, Waryono; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the effect of service quality on customer satisfaction in tourist object minang fantasi Padang Panjang city. Variabel research is service quality and customer satisfaction. Population of 24.363 people. And Sampling technique using insidental sampling amounted to 100 people. Data the collected in analysis with simple linear regression test. Based on research that has been done,the result: (1)quality of service are in high category(61.9%), (2)customer statisfaction are in high category(55.5%), (3)results of hypothesis testing simple linear regression f hitung with sig. 0,000 < 0,05, so service quality variables can explain visitor statisfaction significantly, r square of 0,414 wich one the influence of service quality on costumer statisfaction by 41% and 59% influenced by other factors.Keyword: service quality, costumer statisfaction